2012
DOI: 10.1088/0029-5515/52/2/023016
|View full text |Cite
|
Sign up to set email alerts
|

Ion energies and currents of type I and mitigated ELMs in the ASDEX Upgrade far scrape-off layer

Abstract: Abstract. New measurements of ion energies and currents in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 54 publications
5
30
0
Order By: Relevance
“…Illustrative results discussed here appear in more detail in Ref. [25]. Figure 9 shows typical time traces of j sat and I c measured by the RFA in two similar type I ELMs at Δr sep = 35 mm.…”
Section: Far Sol Elm Ion Energiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Illustrative results discussed here appear in more detail in Ref. [25]. Figure 9 shows typical time traces of j sat and I c measured by the RFA in two similar type I ELMs at Δr sep = 35 mm.…”
Section: Far Sol Elm Ion Energiesmentioning
confidence: 93%
“…[21]. Despite of its relative simplicity, the model was previously successful in reproducing a variety of experimental observations in AUG and JET [19,[21][22][23][24][25]. Additionally, in Ref.…”
Section: Ion Energies In Turbulent Plasma Filamentsmentioning
confidence: 99%
“…Since RFEA probes rely on the assumption that the ion distribution measured is Maxwellian, measurements of ELMs can prove difficult. At the target, measurements of ELMs have been attempted by both the SST, as used on AUG [4] and MAST for Lmode filaments [17] and previous ELM measurements on MAST [17], and the FST. Here, two similar sets of type III ELMs are used to compare the two methods.…”
Section: Validation Of Elm Measurements By Rfeamentioning
confidence: 99%
“…Previous measurements made in JET [2], ASDEX Upgrade (AUG) [3] [4]and MAST [5] with retarding field energy analysers (RFEA) have shown that ELMs can carry significant amounts of energetic ions into the far SOL at the mid-plane. For tokamaks with close fitting vessel walls, such as ITER, this can be a significant problem since high thermal loading to first wall and divertor materials may cause damage.…”
Section: Introductionmentioning
confidence: 99%
“…The model was previously employed to study the transport of ELM filaments in JET (e.g. [14,26]) and AUG ( [17,41]). Once the initial filament temperatures and density are specified, their time evolution due to parallel transport to the nearest surface can be calculated.…”
Section: Filament Ion Temperaturementioning
confidence: 99%